Pengaruh Penambahan Serat Kulit Bambu Terhadap Sifat Mekanik Beton - M Edwar Hidayat; Ismeddiyanto Ismeddiyanto; Alex Kurniawandy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Concrete has significant deficiencies, which have a low tensile strength. The addition of fiber is one alternative to overcome these deficiecies. Bamboo fiber is a natural fiber that is readily available and relatively fast growth. Fiber which mixing with concrete only take the smooth skin. This research studies the mechanical properties of bamboo fiber concrete consist of compressive strength, splitting tensile strength, flexural strength. Addition of fiber is one of alternation for enhance the strength of concrete. The specimens consists of cylindrical specimens with a diameter of 150 mm and a height of 300 mm and a beam with a length of 600 mm, width 150 mm, and a height of 150 mm. The lenght of fiber that used is 2,5 cm with variation of fiber mass 0,2%, 0,4%, 0,6%, 0,8% 1 % of aggregate fraction.The concrete without fiber is make for comparation. Methods of mixing fibers into the concrete mix in a random way after the concrete is mixed evenly. The result of research showed the compressive strenght, splitng tensile strenght and flexural strength maximum in fiber variation 0,6%. According to the result of research, additional bamboo skin fiber into concrete mixture can improve the mechanical properties of concrete and at optimal fiber variation can on 0.6%.Keywords : fiber concrete, bamboo skin, compressive strenght, splitting tensile strength, flexural strength